Melt season dynamics in a High Arctic estuarine tidal flat: A microbial perspective - Handler, Eleanor Ruth (UiT Norges arktiske universitet, 2022)
The substantial influx of freshwater to High Arctic coastal ecosystems influences nutrient, organic matter, and sediment dynamics, stratification, and light availability throughout the melt season. These changes shape pelagic microbial community composition and functioning, though little is known about impacts on nearshore benthic bacteria. Globally, mudflats are hotspots for biogeochemical cycling, and expected climate change driven increases in terrestrial runoff to coastal areas have highlighted a need to understand the influence these inputs from land might have on Arctic estuarine tidal flat bacteria. In this study, I investigated microbial community composition and function in an estuarine tidal flat through a full melt season, using a combined approach of metabarcoding and carbon-source utilization assays under different salinity treatments. I found that bacterial communities varied through both space and time, as environmental conditions shifted due to riverine inputs and local processes, with salinity as a key structuring gradient. Arctic freshwater bacteria demonstrated higher capacities for degrading a wider range of carbon substrates than Arctic marine microbial communities, indicating higher potential for degradation of complex terrestrially derived organic material in freshwater systems. Terrestrial and riverine taxa were transported with melt water and deposited in sediments, composing up to 60% of sequences in downstream communities. However, their unique functional capabilities appear to be inhibited by the high salinities found in subtidal mudflats, and the highest potential for utilization of terrestrially derived organic matter may be limited to areas where sediments are permeated by freshwater. With anticipated increases in riverine discharge and permafrost thaw in a warming Arctic, tidal flats will likely be more frequently inundated with freshwater and the resident bacteria will have increased access to bioavailable terrestrial organic matter, extending the region where terrestrial organic ...